(untitled) (Materiali di Estetica. Terza serie, 2016)
Getting acquainted with a Philosopher as a Neighbour can be a very delicate experience. Relatedness, closeness, friendship became interwined with political and professional opinions: a non philosopher can grasp some of Guido D. Neri’s work through his living experience. Tolerance and strictness in his thinking could became a good nature experience in everyday life. Some episodes and vignette give a rendering of his person as a thinker , and viceversa. Guido is still an excellent Neighbour.